Pengaruh Perputaran Piutang, Penjualan, Perputaran Kas, Perputaran Persediaan dan Hutang Terhadap Laba Bersih - Bayu Wulandari; Wilda Afriany Ompusunggu (COSTING : Journal of Economic, Business and Accounting, 2021)
This research is a quantitative study which aims to determine the effect of accounts receivable turnover, sales, cash turnover, inventory turnover and debt on the net profit of large trading companies. The study population includes 62 large trading companies listed on the Indonesia Stock Exchange for the period 2016-2018. The sample was determined using purposive sampling method with certain criteria by which 15 companies were obtained so that there were 45 issuers for 3 years. The research data is secondary data obtained from www.idx.co.id and uses multiple linear regression data analysis. The research concludes that accounts receivable turnover, sales, cash turnover, inventory turnover, and debt simultaneously have a significant effect on net profit. Accounts receivable turnover partially has a significant effect on net profit. Sales partially have a significant effect on net profit. Cash turnover partially has a significant effect on net profit. Inventory turnover partially has a significant effect on net profit. Liability partially does not have a significant effect on net profit. Keywords: Receivables turnover, sales, cash turnover, inventory turnover, debt and net profit.